A Checklist of Macronyssid Species (Mesostigmata: Macronyssidae) From Brazil. Issue 2 (1st December 2020) - Bassini-Silva, Ricardo; Jacinavicius, Fernando de Castro; Huang-Bastos, Matheus; Dowling, Ashley P G; Barros-Battesti, Darci Moraes
Abstract: Macronyssid mites are parasites of reptiles, birds, and mammals. A checklist of macronyssid species of Brazil is provided, containing 13 genera and 26 species collected from 99 host species.